Employee Acceptance of Use: A Precondition for Enhancing Therapy Effectiveness, Patient Safety, and Economic Efficiency - von Eiff, Maximilian C.; von Eiff, Wilfried; Roth, Andreas; Ghanem, Mohamed (Frontiers in Public Health, 2019)
Introduction: From the workplace engineering sciences, it is evident that work efficiency, measured by the criteria efficiency and effectiveness of therapy, economy and patient safety, is determined mainly by staff acceptance of new technology and reengineered workflows. Accordingly, the aim of this study was to ascertain and assess differences in terms of the acceptance of alternative types of prosthesis instrument configurations, oriented around the research question: “Which product features and process effects determine a high level of employee acceptance of use?” Materials and Methods: This study is designed as a before-and-after comparison, based on the usability engineering approach. In the first study phase, 46 employees participating in the process of providing instruments for a total knee arthroplasty (TKA) procedure were asked to examine the current working situation, using a standard instrumentation set, in terms of instrument handling, work burden, proneness to errors, patient risks, process efficiency, and effectiveness. In the second study phase, 20 weeks after having implemented a size-specific instrumentation set, the same 46 individuals were surveyed on the identical questions. Additionally, in both study phases the time needed to perform the sub-processes related to instrumentation logistics inside the operating room (OR) was measured, in order to identify process efficiency and cost-saving effects. Results: By using standard sets only 30% perceived a need for improvement. After 20 weeks, only 8% of the employees were satisfied with the previous equipment and 69% regarded the standard set as being relatively error-prone, endangering patient safety. In addition, 85% regarded the effectiveness of the standard process as limited. Finally, 75% considered the effectiveness of the reengineered process to be significantly higher, and 69% drew attention to the reduction of handling disadvantages. Furthermore, the time needed for instrumentation logistics inside the OR estimated at about 13 min less when using size-specific sets. This effect on process efficiency cost savings or the generation of additional revenue by performing additional procedures. Based on these findings, an ergonomic decision-making model has been developed. Conclusion: Innovative medical products such as size-specific instrumentation sets contribute to lower procedure costs and improved process efficiency in the operating room (OR). However, employee motivation to use a new technology as part of an optimized workflow organization, is crucial to achieving an enhanced level of effectiveness, efficiency and patient safety. Hence, it is advisable to enhance change-management efforts in order to reduce resistance to change and ensure the new technology is successful.